New Osmylopsychopid Taxa from the Middle Jurassic of Northeastern China (Neuroptera: Osmylopsychopidae) - Xiaotian Liu; Dong Ren; Chungkun Shih; Yongjie Wang (Insects, 2023)
One new genus with four new species sharing the similar character of a forewing length of ca. 10 mm, namely, Minipsychops spasulus gen. et sp. nov., Minipsychops polychotomus sp. nov., Minipsychops densus sp. nov., and Minipsychops unicus sp. nov., are described from the Middle Jurassic Jiulongshan Formation of Daohugou, Inner Mongolia in China. These new insects can be attributed to Osmylopsychopidae for their distinctive configuration of costal space and the venations of RP1 and Cu. Compared with the typically medium to large body sizes of known osmylopsychopids, these new Middle Jurassic taxa of a particularly miniaturized lineage not only enrich the species diversity of Osmylopsychopidae, but also enhance our understanding of the historical evolution of these poorly known lacewings.